Effect of N-Methyl-D-Aspartate Receptor Antagonist Dextromethorphan on Opioid Analgesia in Pediatric Intensive Care Unit - Mohammed Naeem; Hala Al Alem; Ali Al Shehri; Majed Al-Jeraisy (Pain Research and Management)
Objective. Pain control is an essential goal in the management of critical children. Narcotics are the mainstay for pain control. Patients frequently need escalating doses of narcotics. In such cases an adjunctive therapy may be beneficial. Dextromethorphan (DM) is NMDA receptor antagonist and may prevent tolerance to narcotics; however, its definitive role is still unclear. We sought whether dextromethorphan addition could decrease the requirements of fentanyl to control pain in critical children. Design. Double-blind, randomized control trial (RCT). Setting. Pediatric multidisciplinary ICU in tertiary care center. Patients. Thirty-six pediatric patients 2–14 years of age in a multidisciplinary PICU requiring analgesia were randomized into dextromethorphan and placebo. The subjects in both groups showed similarity in most of the characteristics. Interventions. Subjects while receiving fentanyl for pain control received dextromethorphan or placebo through nasogastric/orogastric tubes for 96 hours. Pain was assessed using FLACC and faces scales. Measurements and Main Results. This study found no statistical significant difference in fentanyl requirements between subjects receiving dextromethorphan and those receiving placebo (p=0.127). Conclusions. Dextromethorphan has no effect on opioid requirement for control of acute pain in children admitted with acute critical care illness in PICU. The registration number for this trial is NCT01553435.